2013
DOI: 10.5114/aoms.2013.39795
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of tissue factor in patients with abdominal aortic and iliac arterial aneurysms – preliminary study

Abstract: IntroductionThe decision on the time and choice of strategy of treatment of abdominal aortic aneurysm must be especially carefully balanced. The aim of the study was to evaluate the tissue factor (TF) plasma level as a potential factor useful in anticipation of abdominal aortic aneurysm and/or iliac arterial aneurysm via comparison of plasma TF level in patients with ruptured and non-ruptured aneurysms.Material and methodsThe study included 33 patients with aneurysm (17 operated on electively because of non-ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…The role of TF as a prognostic factor in AAA rupture was previously studied by Skóra and co-workers revealing higher levels of TF and TFPI in AAA patients [6]. We have also found elevated levels of TF and TFPI in AAA patients compared to the reference group (Table 2), indicating activation of coagulation process in the aorta wall.…”
Section: Resultssupporting
confidence: 64%
“…The role of TF as a prognostic factor in AAA rupture was previously studied by Skóra and co-workers revealing higher levels of TF and TFPI in AAA patients [6]. We have also found elevated levels of TF and TFPI in AAA patients compared to the reference group (Table 2), indicating activation of coagulation process in the aorta wall.…”
Section: Resultssupporting
confidence: 64%
“…However, atherosclerosis may be a potential confounder in these studies, since the polymorphisms identified in these reports have been shown to be also associated with other cardiovascular diseases. Similarly, shared disease pathways between AAA and atherosclerosis may contribute to failure of studies, that focus on AAA-specific biomarkers 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that disease groups, such as cancer, bacterial, and viral infections, and cardiovascular diseases had increased levels of TF-like antigen measured by Imubind [ [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] ] or Quantikine [ 46 , 58 , 59 ] compared with healthy controls ( Table ). These studies report statistically significant increases in TF-like antigen in different disease groups using the Imubind and Quantikine ELISAs.…”
Section: Discussionmentioning
confidence: 99%